Enhancing the RC4 algorithm by eliminating the Initiative Vector (IV) transmission - Waleed Abdelrahman Yousif Mohammed; Salmah Fattah; Khalid Mohammed Osman Saeed; Ashraf Osman Ibrahim Elsayed; Safaa Eltahier (Engineering, Technology & Applied Science Research, 2025)
The Rivest Cipher RC4 encryption algorithm is commonly utilized to generate keys of varying lengths. Despite its rapid processing speed, vulnerabilities within the algorithm have made it susceptible to exploitation, allowing attackers to compromise it within a matter of minutes. This paper introduces an innovative approach to address the vulnerabilities of the RC4 encryption algorithm by employing an Initiative Vector (IV). The proposed method incorporates a lengthy random text without transmitting an initialization vector. The proposed solution was rigorously validated, demonstrating performance comparable to existing solutions while simultaneously expanding the range of potential solutions and mitigating security threats. Further exploration into the use of a complex equation is recommended for calculating the swapping value j while maintaining the same high level of performance.